Preventive Maintenance Mesin Filling Sachet Dalam Mengurangi Downtime Dan Menjaga Produktivitas Di PT. Centa Brasindo Abadi - Muhamad Ryan Agustin; Desmira Desmira (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Centa Brasindo Abadi (CBA) is a company operating in the agricultural sector. To maintain and increase productivity, maintenance of production machines is required. Preventive Maintenance (PM) is an approach used in maintaining equipment and machines to prevent unwanted damage or failure. A sachet filling machine is a machine for packaging products that will be distributed in sachet packaging according to the predetermined product weight. Preventive maintenance helps identify potential problems, saves on costly repairs, and keeps equipment in optimal operational condition. The aim of this research is to determine the implementation of preventive maintenance to maintain productivity in an effort to reduce downtime.